Pengaruh Product Quality, Brand Image, dan Customer Satisfaction terhadap Customer Loyalty Sepatu Lari Outseight di Jakarta - Sapto, Satria; Wijaya, Erric; Nasim, Muhammad (Jurnal Keuangan dan Perbankan, 2024)
One intriguing aspect within the field of running in Indonesia, particularly in Jakarta, is the development of locally-branded running shoes that offer quality nearly on par with international brands. Given the substantial interest among running enthusiasts ini Jakarta, this has prompted researchers to delve further into the consumer loyalty towards local running shoes, particularly those under the Ortuseight brand. The aim of this study is to analyze the impact of product quality, brand image, and customer satisfaction on customer loyalty towards Ortuseight running shoes. This research employs a quantitative approach, collecting through an online questionnaire completed by 133 members of the running community in Jakarta. The analysis utilize multiple linear regression method. The findings of the study indicate that product quality, brand image, and customer satisfaction have a positive and significant influence on customer loyalty towards local running shoes, specifically Ortuseight